Influence of post-deposition annealing time on oxygen gas sensing behaviour of Al/La0·50Ce0·50O1·75/Si metal-oxide-semiconductor capacitor. (8th December 2014) - Lim, W. F.; Cheong, K. Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Effects of post-deposition annealing temperature (400–1000°C) towards sensing performance of a Si-based metal-oxide-semiconductor gas sensor in regard to oxygen gas have been investigated by utilising La0·50Ce0·50O1·75 as the catalytic oxide. The highest sensitivity and best recovery have been obtained by the sensor with its oxide post-deposition annealed at 1000°C. This was associated with the presence of more oxygen vacancies in the oxide that have served as adsorption sites for the oxygen gas molecules. The gas molecules would be adsorbed and dissociated to active oxygen species, which would cause a shift in the current–gate voltage curve to lower current level during gas flow. Response time and recovery time of the sensor were calculated, discussed and explained based on the presence of oxygen vacancies in the oxide.